Modelling Exchange Rate Volatility by Macroeconomic Fundamentals in Pakistan - Munazza Jabeen; Saud Ahmad Khan (International Econometric Review (IER), 2014)
What drives volatility in foreign exchange market in Pakistan? This paper undertakes an analysis of modelling exchange rate volatility in Pakistan by potential macroeconomic fundamentals well-known in the economic literature. For this, monthly data on Pak Rupee exchange rates in the terms of major currencies (US Dollar, British Pound, Canadian Dollar and Japanese Yen) and macroeconomics fundamentals is taken from April, 1982 to November, 2011. The results show thatthe PKR-USD exchange rate volatility is influenced by real output volatility, foreign exchange reserves volatility, inflation volatility, and productivity volatility. The PKR- GBP exchange rate volatility is influenced by foreign exchange reserves volatility and terms of trade volatility. The PKR- CAD exchange rate volatility is influenced by terms of trade volatility. The findings of this paper reveal that exchange rate volatility in Pakistan results from real shocks rather than nominal shocks.
Keywords: F31; C22; 330; Exchange Rate Volatility; GARCH